Preparation and Characterization of Fenofibrate Microparticles with Surface-Active Additives: Application of a Supercritical Fluid-Assisted Spray-Drying Process - Jeong-Soo Kim; Heejun Park; Eun-Sol Ha; Kyu-Tae Kang; Min-Soo Kim; Sung-Joo Hwang (MDPI AG, 2021)
In this study, supercritical fluid-assisted spray-drying (SA-SD) was applied to achieve the micronization of fenofibrate particles possessing surface-active additives, such as d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), sucrose mono palmitate (Sucroester 15), and polyoxyethylene 52 stearate (Myrj 52), to improve the pharmacokinetic and pharmacodynamic properties of fenofibrate. For comparison, the same formulation was prepared using a spray-drying (SD) process, and then both methods were compared. The SA-SD process resulted in a significantly smaller mean particle size (approximately 2 μm) compared to that of unprocessed fenofibrate (approximately 20 μm) and SD-processed particles (approximately 40 μm). There was no significant difference in the effect on the particle size reduction among the selected surface-active additives. The microcomposite particles prepared with surface-active additives using SA-SD exhibited remarkable enhancement in their dissolution rate due to the synergistic effect of comparably moderate wettability improvement and significant particle size reduction. In contrast, the SD samples with the surface-active additives exhibited a decrease in dissolution rate compared to that of the unprocessed fenofibrate due to the absence of particle size reduction, although wettability was greatly improved. The results of zeta potential and XPS analyses indicated that the surface-active additive coverage on the surface layer of the SD-processed particles with a better wettability was higher than that of the SA-SD-processed composite particles. Additionally, after rapid depletion of hydrophilic additives that were excessively distributed on the surfaces of SD-processed particles, the creation of a surface layer rich in poorly water-soluble fenofibrate resulted in a decrease in the dissolution rate. In contrast, the surface-active molecules were dispersed homogeneously throughout the particle matrix in the SA-SD-processed microparticles. Furthermore, improved pharmacokinetic and pharmacodynamic characteristics were observed for the SA-SD-processed fenofibrate microparticles compared to those for the SD-processed fenofibrate particles. Therefore, the SA-SD process incorporating surface-active additives can efficiently micronize poorly water-soluble drugs and optimize their physicochemical and biopharmaceutical characteristics.